Evaluation of Plants and Weeds Extract on the Corrosion Inhibition of Mild Steel in Sulphuric Acid - Abida Begum (E-Journal of Chemistry)
Experiments were performed in order to determine the inhibitive effects of extracts of plants and weeds namely Parthenium hysterophorus, Dathura stromonium, Azadirachta indica, Helianthus annuus leaves extract for mild steel in sulphuric acid by using weight loss and thermometric technique. Results demonstrated that, all the experimental inhibitors show an adsorption on steel surface according to Langmuir’s isotherm. The inhibition efficiency increased with increase in the concentration of all tested inhibitors to attain a maximum value at 1.0%. Free energy values for adsorption process show that the process is spontaneous. The kinetic treatment of the results shows first order kinetics.